Propuesta de mejora para el manejo de inventarios en Ferreaceros Duitama (2022)
The inventories in enterprise constitute an opportunity for improvement affecting operations, customer satisfaction and profitability, one of the ways to address the problem is the comprehensive ma nagement of inventories, the company Ferreaceros has three warehouses and its inventory system presents difficulties; The objective of this project is to identify the best inventory policy for the organization. Three phases are developed through a mixed, d vii escriptive, inductive diagnostic methodology, the data to be treated are mainly numerical and its analysis and projection foundations are mathematical, for this reason this document preserves the quantitative methodology, however it is considered mixed whe n establishing also parameters and characteristics of its operation, the descriptive foundation of this project is established in the documentation and analysis of the organization, its operation of Ferreacaeros SAS, its features in the operations when exe cuting processes in coordination of three wineries, it is considered inductive when establishing the concepts general inventory and establish the parameters applicable to the organization. As a result of this project, the processes were identified with the ir levels of operation, the management developed by the company, and improvements were proposed in accordance with the processes and operations of the organization. It is concluded that Ferreaceros has opportunities for improvement in comprehensive invento ry management, in this same sense, operations affect economic performance and customer satisfaction. The company is recommended to implement the proposals developed for this project in order to improve the comprehensive management of its inventories.